Shifting Chemical Equilibria in Flow—Efficient Decarbonylation Driven by Annular Flow Regimes1. Issue 43 (4th September 2014) - Gutmann, Bernhard; Elsner, Petteri; Glasnov, Toma; Roberge, Dominique M.; Kappe, C. Oliver
Abstract To efficiently drive chemical reactions, it is often necessary to influence an equilibrium by removing one or more components from the reaction space. Such manipulation is straightforward in open systems, for example, by distillation of a volatile product from the reaction mixture. Herein we describe a unique high‐temperature/high‐pressure gas/liquid continuous‐flow process for the rhodium‐catalyzed decarbonylation of aldehydes. The carbon monoxide released during the reaction is carried with a stream of an inert gas through the center of the tubing, whereas the liquid feed travels as an annular film along the wall of the channel. As a consequence, carbon monoxide is effectively vaporized from the liquid phase into the gas phase and stripped from the reaction mixture, thus driving the equilibrium to the product and preventing poisoning of the catalyst. This approach enables the catalytic decarbonylation of a variety of aldehydes with unprecedented efficiency with a standard coil‐based flow device.